History and Effect of South China Sea Conflict on Southeast Asia Political Stability - Saiful Anwar Matondang; Muhammad Ricky Hardiansyah; Surya Aymanda Nababan (Yupa: Historical Studies Journal, 2022)
The purpose of this study is to describe the history and influence of the South China Sea conflict on the political stability of Southeast Asia. The South China Sea has tremendous potential, both in the sea and above the sea. Thus, countries in Southeast Asia and the two major world powers, namely the United States and the People's Republic of China, are trying to claim or at least maintain their influence in the region. This research method uses literature research, and data analysis techniques used use content analysis methods. The findings of this study are that mutual claims between countries in Southeast Asia will become a major conflict in the future if it is not resolved. The negotiations were about the process of resolving conflicts that occurred in the South China Sea in reviewing the problems, and prospects in the South China Sea area for the benefit of all countries.